Phytochemical Analysis and Antimicrobial Activity of Mimordica Charantia Medicinal Plant Against Selected Common Human Pathogenic Microorganisms - Sonali V. Padwad; Ashish P. Lambat; Prachi A. Lambat; Ankita R. Chaudhary; Ashish D. Tiple (International Journal of Pharma and Bio Sciences, 2022)
Momordica charantia is a plant belonging to Cucurbitaceae family known for decades for its medicinal and nutritional value. The objective of the present study was to do qualitative evaluation and compare the antibacterial activity of M. charantia leaf, seeds and fruits. Results of our study showed that hybrid seed methanol extract had more active phytoconstituents like alkaloid, carbohydrate, saponin, proteins, resin, flavonoid, diterpens, reducing sugars than other extracts of fruit, leaf and seed of wild and hybrid varieties of M. charantia extracted using different solvents. Carbohydrate, phytosterol, and proteins are mostly present in all extracts of Mimordica charantia. Flavonoids are significantly present in seeds. So hybrid seed methanol extract can be considered as the main source of above mentioned phytochemicals to facilitate pharmaceutical industries. Methanol extracts of hybrid seed exhibited highest zone of inhibition against Salmonella paratyphi A (30±0.64mm) & Staphylococcus aureus (26±0mm) and chloroform extract of wild fruit showed highest activity against E.coli (22.5±0.64mm).Hence these extracts may be used to treat infectious diseases, surgical wounds, skin lesions, salmonellosis, enteric fever, food poisoning. The purpose of the current study was to investigate antimicrobial activity of M. charantia, apart from being used as anti-psoriatic drugs and this plant earlier have been used also as antibacterial agents, hence the activity was also carried out against other organisms such as Escherichia coli, Staphylococcus aureus, Bacillus subtilis, Salmonella typhi and Aspergillus niger. Further phytochemical analysis (using techniques like TLC and HPLC) will be necessary to isolate the active constituents and clinical studies are required to understand the mechanism and the actual efficacy of these extracts in treating various infections and skin diseases. This will have significant importance in pharmaceutical and herbal industries.